Facets of Self-Consciousness. - Edited by Katja Crone, Kristina Musholt & Anna Strasser (Grazer philosophische Studien ;, 2012)
This special issue of Grazer Philosophische Studien brings together a number of carefully selected and timely articles that explore the discussion of different facets of self-consciousness from multiple perspectives. The selected articles mainly focus on three topics of the current debate: (1) the relationship between conceptual and nonconceptual ways of self-representation; (2) the role of intersubjectivity for the development of self-consciousness; (3) the temporal structure of self-consciousness. A number of previously underexposed, yet important connections between different approaches are.